2020
DOI: 10.1186/s12891-020-03478-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between muscle strength and depressive symptoms among Chinese female college freshmen: a cross-sectional study

Abstract: Background: Increased physical activity level is related to lower risk of depressive symptoms, and there is an inverse association between muscle strength and risk of depressive symptoms among the elderly. Although there is evidence of an inverse association between muscle strength and depressive symptoms, the relationship between these variables in a younger population is still unknown. This study aimed to examine the association between handgrip strength, a representative indicator of skeletal muscle strengt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
2
4
0
1
Order By: Relevance
“…Furthermore, individuals in the highest explosive fitness level had less than half the associated risk of depression than individuals in the lowest levels. This is a particularly interesting finding as it appears to suggest that different types of fitness than those reported elsewhere (Ren et al, 2020) may have an effect of protection from depressive symptoms. Future prospective cohort or intervention studies are required to better elucidate the relationships between explosive fitness and the risk of depressive symptoms.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Furthermore, individuals in the highest explosive fitness level had less than half the associated risk of depression than individuals in the lowest levels. This is a particularly interesting finding as it appears to suggest that different types of fitness than those reported elsewhere (Ren et al, 2020) may have an effect of protection from depressive symptoms. Future prospective cohort or intervention studies are required to better elucidate the relationships between explosive fitness and the risk of depressive symptoms.…”
Section: Discussionsupporting
confidence: 51%
“…Associations between fitness measures and depressive symptoms in young adults may be bidirectional. Studies have indicated that previous depression could be a factor in the cessation of exercise, and the development of a sedentary lifestyle since those with depression may have lower self-worth, and confidence, increased self-criticism, and unwarranted guilt (Faulkner, Carson & Stone, 2014;Ren et al, 2020). Future prospective cohort or intervention studies are required to better elucidate the relationships between fitness, particularly anaerobic and explosive fitness, and the risk of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that this is the first study focused on the role of self-esteem in the association between muscular strength and risk of depression in adolescents, our results partially concur with previous data analysing muscular strength and depression showing null associations in children (Esmaeilzadeh, 2014;Rodriguez-Ayllon et al, 2018). However, significant inverse associations were found between muscular strength and depression in adults (Ashdown-Franks et al, 2019;Ren et al, 2020;Wu et al, 2017). We speculate that this lack of association could be explained by the fact that our participants did not achieve the highest maturity stage (i.e.…”
Section: Discussionsupporting
confidence: 89%
“…However, limited study focus on young people especially on college students. To our best knowledge, we find one study indicated that handgrip strength is inversely and independently related to the risk of depressive symptoms among Chinese girls college, while the Chinese boys college were not involved ( 17 ).…”
Section: Introductionmentioning
confidence: 99%